FENOMENA KORBAN LUMPUR, TINDAKAN KOLEKTIF, PRODUKSI IDENTITAS DAN FENOMENOLOGI - G.M. Sukamto (Jurnal Sejarah dan Budaya, 2013)
Abstract. Dreadfulness of Lapindo mud is one of phemonenal tragedies in Indonesia. Most horrifying talked about the victim, they are suffering and being deeply hurts. Extremely, Lapindo mud was not much horrendous as tsunami tragedy, but these phenomenon takes the long times to cure all the pain. With phenomenology, victim identity will segmented by many factors. There are about natural, structural and cultural segmented. Composing conspiration between actor and strategy hold this phenomenon getting worst.